Investigation on the Mechanical Properties of Powder Metallurgy-Manufactured AA7178/ZrSiO4 Nanocomposites - R. Srinivasan; S. Karunakaran; M. Hariprabhu; R. Arunbharathi; S. Suresh; S. Nanthakumar; S. K. H. Ahammad; S. Mayakannan; Mani Jayakumar (Advances in Materials Science and Engineering)
The versatility of metal matrix composites (MMCs) makes them a promising material for various industrial applications. The current study used a ball milling to mechanically AA7178 powder and strengthened with zirconium silicate (ZrSiO4) nanoparticles. In addition, the AA7178 matrix was ball-milled to distribute the ZrSiO4 nanoparticles throughout the material. The AA7178 reinforced with ZrSiO4 nanoparticles was compacted and consolidated using two distinct powder metallurgy (PM) sequences: double pressing, double sintering, and hot pressing. In tests measuring microhardness, compression strength, and elongational break, the new nanocomposites surpassed the AA7178. The adequate interfacial bonding and even distribution of ZrSiO4 nanoparticles throughout the AA7178 matrix were essential to the strengthening mechanism. With the use of hot pressing, the mechanical characteristics of the nanocomposites were enhanced. As reinforcement concentration increased beyond 2.5% by weight, mechanical properties drastically degraded due to ZrSiO4 nanoparticles clumping and unequal distribution. Improved mechanical parts attain through the uniform distribution of ZrSiO4 nanoparticles in the AA7178 and the maintenance of their mechanical properties.